First prospective clinical evaluation of feasibility and patient acceptance of magnetic resonance-guided radiotherapy in Germany - Klüter, Sebastian; Katayama, Sonja; Renkamp, Claudia Katharina; Körber, Stefan A.; Major, Gerald; Alber, Markus; Akbaba, Sati; Debus, Jürgen; Hörner-Rieber, Juliane (Strahlentherapie und Onkologie, 2020)
Magnetic resonance-guided radiotherapy (MRgRT) has recently been introduced in our institution. As MRgRT requires high patient compliance compared to conventional techniques and can be associated with prolonged treatment times, feasibility and patient tolerance were prospectively assessed using patient-reported outcome questionnaires (PRO-Q).
Gesehen am 25.11.2021